2023
DOI: 10.4314/ijest.v14i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals content and in-vitro antioxidant properties of Azadirachta indica seeds, leaves and twigs prepared from different extraction techniques

Abstract: The current study was design to exploit the Azadirachta indica leaves, seeds and twigs for %yield, phytochemicals content and antioxidant activities using infusion, hydroalcoholic, decoction and microwave extraction techniques. The phytochemicals contents were determined by standard reported methods. While antioxidant activity was assessed by three (03) standards In-vitro antioxidant test systems as 1, 1’-diphynyl- 2-picrylhydrazyl (DPPH), Hydrogen peroxide (H2O2) scavenging activity and Nitric oxide (NO) scav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Our study showed that infusion is more efficient, simple, does not use toxic and flammable solvents, and required no more heat and temperature as compared to the decoction and microwave extraction methods. The infusions were more active than decoctions; it strengthens the principle that not only the applied solvent is crucial; but also the process of extraction is also important (Ali et al, 2022). During decoction, the bioactive compounds might be damaged or partially inactivated by providing the high temperature to the plants materials.…”
Section: Quantification Of Bioactive Compounds In Azadirachta Indica ...mentioning
confidence: 78%
See 2 more Smart Citations
“…Our study showed that infusion is more efficient, simple, does not use toxic and flammable solvents, and required no more heat and temperature as compared to the decoction and microwave extraction methods. The infusions were more active than decoctions; it strengthens the principle that not only the applied solvent is crucial; but also the process of extraction is also important (Ali et al, 2022). During decoction, the bioactive compounds might be damaged or partially inactivated by providing the high temperature to the plants materials.…”
Section: Quantification Of Bioactive Compounds In Azadirachta Indica ...mentioning
confidence: 78%
“…Infusion was observed to be the most efficient extract system followed by microwave and decoction to extract the phytochemicals. The infusion displayed highest activity than decoction (Sandipta et al, 2021;Ali et al, 2022).…”
Section: Quantification Of Bioactive Compounds In Azadirachta Indica ...mentioning
confidence: 99%
See 1 more Smart Citation